Cytochromes P450 and experimental models of drug metabolism - Zuber, R. (J Cell Mol Med, 2007)
For the development of new drugs, evaluation of drug‐drug interactions with already known compounds, as well as for better understanding of metabolism pathways of various toxicants and pollutants, we studied the drug metabolism mediated by cytochromes P450. The experimental approach is based on animal drug‐metabolising systems. From the ethical as well as rational reasons, the selection of an appropriate system is crucial. Here, it is necessary to decide on the basis of expected CYP system involved. For CYP1A‐mediated pathways, all the commonly used experimental models are appropriate except probably the dog. On the contrary, the dog seems to be suitable for modelling of processes depending on the CYP2D. With CYP2C, which is possibly the most large and complicated subfamily, the systems based on monkey (Maccacus rhesus) may be a good representative. The CYP3A seems to be well modelled by pig or minipig CYP3A29. Detailed studies on activities with individual isolated CYP forms are needed to understand in full all aspects of inter‐species differences and variations.